O zanikanju in nikalnici v slovenščini - Ilc, Gašper (Jezik in slovstvo, 2008)
The article deals with negation in Slovene from a cross-linguistic perspective, focusing on its syntactic and semantic characteristics. On the basis of the classification of negation by Ö. Dahl (1979), we demonstrate thatthe Slovene negator ne shows characteristics of both the morphological andsyntactic types of negation. Following the well-established classification of negative elements (e.g., Haegeman 1995), we find that Slovene negative pronouns best fit the category of so-called Negative Concord Items (NCI) that are morphologically derived from interrogative pronouns. In the process of syntactic derivation (Slovene) negative pronouns enter into an agreement relationship with the sentence negator ne that we interpret as single negation. From a semantic point of view we call this relationship negative concord and we distinguish it from the other three possible interpretations ofmultiple negation: double negation, litotes and emphatic negation.
Keywords: denial; grammar; nikalnice; skladnja; Slovene; slovenščina; slovnica; syntax; zanikanje